Authorship ignorance: views of researchers in French clinical settings. Issue 10 (30th September 2005) - Pignatelli, B; Maisonneuve, H; Chapuis, F
Abstract : Objectives: To assess the knowledge and behaviour of researchers regarding criteria for authorship, and the practices of ghost and gift authorship. Design: Semidirective interviews of senior clinical researchers. Setting: University hospital. Participants: Thirty-nine main investigators of clinical research programmes. Main measurements: Awareness and use of International Committee of Medical Journal Editors (ICMJE) criteria for authorship, and perceptions about ghost and gift authorship. Results: A total of 48 protocols submitted by 42 principal investigators between 1994 and 1996 were identified. Thirty-nine investigators were contacted; 37 (one of whom delegated a co-author) were interviewed between May 2002 and March 2003. Two co-authors of two principal investigators were also interviewed. In all, 42 studies were represented. The interviews lasted for 40–90 minutes and were conducted with openness and respect for confidentiality. The choice of names of co-authors did not follow the ICMJE recommendations. Half of the respondents stated they were aware of criteria for authorship and knew of ICMJE, but most of them did not cite any of the ICMJE criteria among those they applied in deciding authorship. Most of them disagreed with the obligation to meet the three criteria justifying co-authorship because they found these too rigid and inapplicable. Gift authorship was a common practice; 59% of the respondents had been a recipient of gift authorship. Twenty-five (64%) were aware of ghost authorship and the majority considered it questionable and blameworthy. Conclusions: The ICMJE criteria were ignored by clinicians at a university hospital. Ghost and gift authorship were frequent among them. There is a need for French guidelines for authorship to be prepared and implemented.